2020
DOI: 10.1007/s40199-019-00321-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of tyrosine kinase inhibitors in chronic myeloid leukemia; a clinician’s perspective

Abstract: Objective In this review, we have summarized the pharmacokinetics, pharmacodynamics and adverse effects of imatinib, dasatinib, nilotinib, bosutinib, ponatinib and radotinib with focus on pharmacogenomic studies with clinical end points. We have discussed the key phase 3 trials of tyrosine kinase inhibitors (TKI) comparing with each other, treatment free remission (TFR) and selection of TKI. Upcoming concepts and related trials in the management of chronic myeloid leukemia (CML) along with future directions ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 109 publications
0
10
0
Order By: Relevance
“…Kernel-density probability estimates for unmixed deposit spectra revealed that each detectable xenobiotic exhibited unique drug-biomolecule complexes as determined by the relative abundance of lipid/protein in each voxel ( Figures 4 A–4D). This allowed us to elucidate xenobiotic-cell interactions in 3D iHLC, showing for example that amiodarone (a known lipophilic drug with a long half-life of >60 days 39 ) would faithfully accumulate in lipid-rich subcellular voxels, while the nilotinib spectra (also being lipophilic but having a considerably shorter half-life of 17 h 46 ) would be detected in protein-rich voxels, indicating metabolic processing. Neratinib spectra, in contrast, accumulated in voxels that are neither protein nor lipid rich.…”
Section: Resultsmentioning
confidence: 99%
“…Kernel-density probability estimates for unmixed deposit spectra revealed that each detectable xenobiotic exhibited unique drug-biomolecule complexes as determined by the relative abundance of lipid/protein in each voxel ( Figures 4 A–4D). This allowed us to elucidate xenobiotic-cell interactions in 3D iHLC, showing for example that amiodarone (a known lipophilic drug with a long half-life of >60 days 39 ) would faithfully accumulate in lipid-rich subcellular voxels, while the nilotinib spectra (also being lipophilic but having a considerably shorter half-life of 17 h 46 ) would be detected in protein-rich voxels, indicating metabolic processing. Neratinib spectra, in contrast, accumulated in voxels that are neither protein nor lipid rich.…”
Section: Resultsmentioning
confidence: 99%
“…?, reduced the effect of the treatment force. 37 The treatment force for TKI system, , and , were defined as the following, In the model, the transition from normal potential to CML potential was approximated using three critical points using c 1 , c 2 and c 5 as ∇ U p-CML = a ( x – c 1 )( x – c 2 )( x – c 5 ), and…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, BCR::ABL1-independent mechanisms, including BCR :: ABL1 amplification and clonal evolution of CML clones, have been reported in CML with TKI resistance, albeit at lower frequencies [18] , [19] , [20] . BCR::ABL1-independent mechanisms can also consist of the impairment of specific TKI transporters (influx and efflux transporters), an inappropriate concentration of TKIs, dysregulation of alternative signaling pathways of CML cells, and epigenetics [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] . Recently, there has been evidence indicating that mutations in genes involved in the tumorigenesis of myeloid leukemia, such as DNMT3A and ASXL1 , IDH1 , and SETBP1, are associated with the resistance to TKIs therapy in CML without BCR :: ABL1 kinase domain mutations [29] , [30] .…”
Section: Introductionmentioning
confidence: 99%